2018
DOI: 10.1371/journal.pone.0198442
|View full text |Cite
|
Sign up to set email alerts
|

The proteome of perilymph in patients with vestibular schwannoma. A possibility to identify biomarkers for tumor associated hearing loss?

Abstract: BackgroundDue to the surrounding bone, the human inner ear is relatively inaccessible and difficult to reach for cellular and molecular analyses. However, these types of investigations are needed to better understand the etiology, pathophysiology and progression of several inner ear disorders. Moreover, the fluid from the inner ear cannot be sampled for micro-chemical analyses from healthy individuals in vivo. Therefore, in the present paper, we studied patients with vestibular schwannoma (VS) undergoing trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…On the other hand, of the 91 commonly identified perilymph proteins of patients with VS on an individual level, Rasmussen et al described four proteins that were significantly associated with tumor-related deafness: Immunoglobulin (Ig) γ-4 chain C region, Ig κ chain C region, complement C3, and immunoglobulin heavy constant γ 3. These 91 proteins were identified in 12 out of 15 samples they used in the study (15), which was confirmed by analogy with data from previous MS research on perilymph (20, 24).…”
Section: Biological Markerssupporting
confidence: 83%
See 3 more Smart Citations
“…On the other hand, of the 91 commonly identified perilymph proteins of patients with VS on an individual level, Rasmussen et al described four proteins that were significantly associated with tumor-related deafness: Immunoglobulin (Ig) γ-4 chain C region, Ig κ chain C region, complement C3, and immunoglobulin heavy constant γ 3. These 91 proteins were identified in 12 out of 15 samples they used in the study (15), which was confirmed by analogy with data from previous MS research on perilymph (20, 24).…”
Section: Biological Markerssupporting
confidence: 83%
“…During an apoptotic or necrotic episode inside the inner ear, the proteins that are secreted can be found at high concentrations in this fluid (20). The knowledge of the perilymph proteome may shed some light on the mechanisms of tumor-associated hearing loss, which are mostly unknown to date (15). Stankovic et al speculated that because of an unknown toxic substance generated by the VS, hearing loss in VS could be linked to a high protein concentration in the perilymph (7).…”
Section: Biological Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence of the difficulty in obtaining samples, perilymph is a relatively unknown sample material in terms of bioanalysis. Most of the literature on the composition of human perilymph has been focused on its proteome content and is limited to patients undergoing surgical interventions (Lysaght et al 2011; Schmitt et al 2017; Edvardsson Rasmussen et al 2018; Palmer et al 2018). Some attention has been directed at characterizing the small metabolites of perilymph using mainly HPLC with fluorescence detection (Drescher, Medina and Drescher 1981; Medina and Drescher 1981; Scheibe and Haupt 1985; Bobbin and Fallon 1992).…”
Section: Introductionmentioning
confidence: 99%